Passive charge state control of nitrogen‐vacancy centres in diamond using phosphorous and boron doping. Issue 10 (1st September 2014) - Groot‐Berning, Karin; Raatz, Nicole; Dobrinets, Inga; Lesik, Margarita; Spinicelli, Piernicola; Tallaire, Alexandre; Achard, Jocelyn; Jacques, Vincent; Roch, Jean‐François; Zaitsev, Alexander M.; Meijer, Jan; Pezzagna, Sébastien
Abstract : The control and stabilisation of the charge state of nitrogen‐vacancy centres in diamond is an important issue for the achievement of reliable processing of spin‐based quantum information. The effect of phosphorous and boron doping of diamond on the charge state of nitrogen‐vacancy (NV) centres is shown here. Ensembles of NV centres are produced at a depth of 60 nm in ultrapure diamond by implantation of nitrogen ions. Overlapping with the NV ensembles, donor and acceptor doped regions of different doping levels are prepared by ion implantation of phosphorus and boron followed by annealing in vacuum at 1500 °C. We show how the charge state of NV centres is controlled by the presence of phosphorous or boron atoms in their neighbourhood. For the lowest doping level, spectral measurements on the ensemble of NV centres reveal a higher amount of NV 0 in the case of boron and a higher amount of NV − in the case of phosphorus, as compared with undoped regions. This behaviour is strengthened when the doping level is increased. Interestingly, the charge state control of native silicon‐vacancy centres is also evidenced. Finally, we discuss the role of the surface termination of diamond on the average charge state of the NV ensemble (still dominant even at a depth of 60 nm) and confirm that the surface 2D‐hole‐gas (H‐termination) can be compensated by nitrogen itself.